Tanshinones, Critical Pharmacological Components in Salvia miltiorrhiza - Jiang, Zhouqian; Gao, Wei; Huang, Luqi (Frontiers in Pharmacology, 2019)
Salvia miltiorrhiza Bunge, a member of the Lamiaceae family, is valued in traditional Chinese Medicine. Its dried root (named Danshen) has been used for hundreds of years, primarily for the treatment of cardiovascular and cerebrovascular diseases. Tanshinones are the main active ingredients in S. miltiorrhiza and exhibit significant pharmacological activities, such as antioxidant activity, anti-inflammatory activity, cardiovascular effects, and antitumor activity. Danshen dripping pill of Tianshili is an effective drug widely used in the clinical treatment of cardiovascular diseases. With the increasing demand for clinical drugs, the traditional method for extracting and separating tanshinones from medicinal plants is insufficient. Therefore, in combination with synthetic biological methods and strategies, it is necessary to analyze the biosynthetic pathway of tanshinones and construct high-yield functional bacteria to obtain tanshinones. Moreover, the biosynthesis of tanshinones has been studied for more than two decades but remains to be completely elucidated. This review will systematically present the composition, extraction and separation, pharmacological activities and biosynthesis of tanshinones from S. miltiorrhiza, with the intent to provide references for studies on other terpenoid bioactive components of traditional Chinese medicines and to provide new research strategies for the sustainable development of traditional Chinese medicine resources.